2003
DOI: 10.2466/pms.2003.97.3.979
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of the Overhand Throw by Undergraduates in Education Using a Distance Learning Computer Program

Abstract: The purpose was to (a) examine whether computer-based distance learning could enhance the qualitative analysis skills (error detection in the overhand throw) of undergraduates in education and (b) examine the effectiveness of several methods of information presentation (video file and text) on distance learning. Participants were randomly assigned to 1 of 4 groups, to detect errors in an incorrect throwing motion of a model on the computer screen. Group 1 (n=13) was the control; Group 2 (n=13) viewed a video o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Eight studies in the Category 3 corpus compared online environments using different media elements such as one-way video (Maag 2004;McKethan et al 2003;Schmeeckle 2003;Schnitman 2007;Schroeder 2006;Schutt 2007;Tantrarungroj 2008;Zhang et al 2006). Seven of the eight studies found no significant differences among media combinations.…”
Section: Media Elementsmentioning
confidence: 99%
“…Eight studies in the Category 3 corpus compared online environments using different media elements such as one-way video (Maag 2004;McKethan et al 2003;Schmeeckle 2003;Schnitman 2007;Schroeder 2006;Schutt 2007;Tantrarungroj 2008;Zhang et al 2006). Seven of the eight studies found no significant differences among media combinations.…”
Section: Media Elementsmentioning
confidence: 99%
“…A number of studies investigated the effects of multimedia elements, simulations and manipulatives within online environments (McKethan et al, 2003;Schmeeckle, 2003;Maag, 2004;Schroeder, 2006;Zhang et al, 2006;Schnitman, 2007;Schutt, 2007;Tantrarungroj, 2008). These studies discovered two important aspects regarding multi-media components within an OLE: (1) Incorporating media components alone is not sufficient by itself to enhance instruction and positively influence learning while they contribute to knowledge retention and (2) how these media components are integrated does play a key role in student learning, e.g.…”
Section: Use Of Multimedia Elements Simulations and Manipulativesmentioning
confidence: 99%
“…when they are interactive. (McKethan et al, 2003;Schmeeckle, 2003;Maag, 2004;Schroeder, 2006;Zhang et al, 2006;Schnitman, 2007;Schutt, 2007;Tantrarungroj, 2008). Media components incorporated to an OLE should predominantly be interactive.…”
Section: Use Of Multimedia Elements Simulations and Manipulativesmentioning
confidence: 99%
“…Eight studies in the Category 3 corpus compared online environments using different media elements such as one-way video (Maag 2004;McKethan et al 2003;Schmeeckle 2003;Schnitman 2007;Schroeder 2006;Schutt 2007;Tantrarungroj 2008;Zhang et al 2006). Seven of the eight studies found no significant differences among media combinations.…”
Section: Media Elementsmentioning
confidence: 99%